2019
DOI: 10.1111/1751-7915.13447
|View full text |Cite
|
Sign up to set email alerts
|

Expression fusion immunogen by live attenuated Escherichia coli against enterotoxins infection in mice

Abstract: Summary Previous epidemiological studies have shown that enterotoxins from enterotoxigenic Escherichia coli (ETEC) appear to be the most important causes of neonatal piglet and porcine post‐weaning diarrhoea (PWD). Thus, it is necessary to develop an effective vaccine against ETEC infection. In the present study, the Kil cassette was inserted into the pseudogene yaiT by homologous recombination to create an attenuated E. coli double selection platform O142(yaiT‐Kil). After that, PRPL‐Kil was replaced with a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Lee et al reported that mice vaccinated with F4 fimbriae that orally delivered with thiolated eudragit microsphere (TEMS) triggered similar levels of IgG1 and IgG2a in mice, indicating a mixed Th1 and Th2 immune responses 29 . While the BALB/c mice orally immunized with a live attenuated ETEC vaccine that express fusion enterotoxins induced a Th2 type response 30 . Our results suggested that delivery methods affected the Th1/Th2 bias in the immune responses to the ETEC total RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that mice vaccinated with F4 fimbriae that orally delivered with thiolated eudragit microsphere (TEMS) triggered similar levels of IgG1 and IgG2a in mice, indicating a mixed Th1 and Th2 immune responses 29 . While the BALB/c mice orally immunized with a live attenuated ETEC vaccine that express fusion enterotoxins induced a Th2 type response 30 . Our results suggested that delivery methods affected the Th1/Th2 bias in the immune responses to the ETEC total RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Feng and Guan (2019) designed a recombinant E. coli strain expressing LTA-STa A13Q -STb-LTA2-LTB-STa A13Q -STb fusion antigen [ 64 ]. Since the LT promoter was preserved, the expression of the fusion protein did not require an inducer.…”
Section: Oral Vaccinesmentioning
confidence: 99%
“…However, more effective is vaccination. [41][42][43] Due to the complex and diverse pathogen serotypes and the poor broad spectrum of traditional vaccines, the effect of treatment is not satisfactory. The disease has always been the focus and difficulty of scholars at home and abroad.…”
Section: Discussionmentioning
confidence: 99%